Excitement and predation at Shoebill nests - Mullers, Ralf HE; Reid, Craig (Biodiversity Observations, 2014)
The cameras were programmed to take a photograph each time the sensor detected movement and the batteries lasted for about a week. Only a few other species than Shoebills were observed near the nests. On two occasions we saw a Sitatunga ...